2012
DOI: 10.1139/z11-126
|View full text |Cite
|
Sign up to set email alerts
|

Genetically modified growth affects allometry of eye and brain in salmonids

Abstract: Effects of growth acceleration on eye development have been examined in genetically modified salmonids. Growth hormone (GH) transgenic coho salmon ( Oncorhynchus kisutch (Walbaum, 1792)) show dramatically elevated overall body growth and an absolute increase in eye size, but relative eye growth is shifted from negatively allometric to more isometric. Thus, transgenic fish possess significantly smaller eyes relative to nontransgenic fish of the same size. Ration-restricted limitation of growth in transgenic sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 49 publications
3
36
0
1
Order By: Relevance
“…Apart from simply being proportional to the head size, Devlin et al (2012) have suggested that the eye development of rapidly growing fish becomes decoupled from their somatic growth, resulting in a negative allometry.…”
Section: Differences Between Wild and Farmed Fishmentioning
confidence: 99%
“…Apart from simply being proportional to the head size, Devlin et al (2012) have suggested that the eye development of rapidly growing fish becomes decoupled from their somatic growth, resulting in a negative allometry.…”
Section: Differences Between Wild and Farmed Fishmentioning
confidence: 99%
“…In a previous study of our laboratory, we had found that transgenic carp had 6.36 times higher serum GH level than the nontransgenic fish (Duan et al, ), which may have resulted in the reduced growth rate of the pharyngeal bone in the transgenic carp. It could be due to a de‐coupling between somatic growth (strongly stimulated by GH) and pharyngeal bone growth (less strongly stimulated by GH) similar to that found for coho salmon eye and brain growth (Devlin et al, ; Kotrschal et al, ).…”
Section: Discussionmentioning
confidence: 57%
“…The criteria used and the scoring outcome strongly suggest that the raters used traits easily recognized from transgenic fish reared only in the hatchery. Typically, fast-growing hatchery-reared transgenic fish have smaller eyes and heads, large, bulging abdomens, and a higher condition factor from the larger amount of food consumed compared to wildtype fish (Ostenfeld et al 1998, Devlin et al 2012. Such changes in phenotype are highly dependent on indirect effects of enhanced growth rate, since the characteristics are much reduced in transgenic animals forced to grow at a wild-type rate by ration restriction (Devlin et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, fast-growing hatchery-reared transgenic fish have smaller eyes and heads, large, bulging abdomens, and a higher condition factor from the larger amount of food consumed compared to wildtype fish (Ostenfeld et al 1998, Devlin et al 2012. Such changes in phenotype are highly dependent on indirect effects of enhanced growth rate, since the characteristics are much reduced in transgenic animals forced to grow at a wild-type rate by ration restriction (Devlin et al 2012). These traits had already developed in the Th group after three months in the hatchery and were still easily observable even after 10 months in the stream environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation